Shodhana and Shamana Chikitsa in Pakshaghata - A Conceptual Study - Alka; Kumar, Parveen; Prakash, Gayathri M; Sharma, Chander Shekhar (International Research Journal of Ayurveda & Yoga, 2022)
Vata Vyadhis (diseases due to vitiated Vata) are becoming most prevalent diseases now a days. Diseases caused by Vata (Dosha responsible for cognition and movement) in its vitiated condition are called Vata Vyadhis. Pakshaghata is one of the Vata Vyadhis which can be correlated with Hemiplegia/Stroke in accordance with the clinical presentation. In the present era due to bad eating habits and sedentary life style, many diseases are manifesting like diabetes mellitus, hypertension etc resulting in more complicated conditions like stroke. A stroke is described as a sudden neurological episode brought on by reduced blood flow to the brain which lasts for more than 24 hours or leading to death, with no probable cause other than a vascular one. Around 1.8 million people in India suffer from stroke every year. According to the modern sciences the brain cells once damaged cannot be repaired and regenerated, resulting in poor prognosis. So the treatment of Pakshaghata (Hemiplegia/Stroke) is challenging in itself. Ayurveda emphasize on three line of treatment i.e Nidana Parivarjana (Avoidance of etiological factors) Shodhana (Purification) and Shamana(Pacification). It has shown by the different studies that Shodhana Chikitsa, Shamana Chikitsa and Pathya Sevan (Intake of Wholesome food) seems to be very effective in alleviating the disease, improving the quality of life of the affected individual. Therefore it is assumed that Nidan Parivarjana, Shodhana and Shamana Chikitsa, will be of great help in alleviating the disease. Keeping the above said fact in mind present the present article emphasizes on the compilation of various Shodhana and Shamana therapies mentioned in the classics of Ayurveda for the management of Pakshaghata.